Facilitators and barriers of service utilization: Perspectives of stakeholders in a family health center of central Kerala - A qualitative study - Sajna Mathumkunnath Vijayan; Safa Puliyakkadi; Swathi Chalil (Wolters Kluwer Medknow Publications, 2021)
Background: Transformation of Primary Health Centers to Family Health Centers (FHC) in Kerala is a new movement. It is important to study the perspectives of stakeholders about it so that strengthening of the facilitators and tackling the barriers can be done. Objectives: The objectives of this study were to understand the perspectives of patients and health-care workers on the facilitators and barriers of service utilization in a FHC in Central Kerala. Methods: Descriptive qualitative study was done for a period of 3 months at FHC, Mundur, Thrissur district, Kerala. In-depth interview of medical officer, health supervisor, and accountant was conducted. Two focus group discussions at the FHC among Accredited Social Healthcare Activists (ASHAs) and patients and one among community members were done. The Attride-Stirling's thematic network analysis framework was followed for data analysis. The findings are reported in accordance with Consolidated Criteria for Reporting Qualitative Research guidelines. Results: The facilitators identified for service utilization are good behavior of staff, evening outpatient department and special clinics, improved infrastructure and clean premise, trust in ASHA workers, subsidized laboratory service, local self-government involvement, funds, and rewards. The barriers of service utilization are staff shortage and workload, lack of awareness among general population about some services, and shortage of medicines. Conclusion: The concept of FHC is agreeable to both the health-care workers and the community. The barriers can be tackled at this stage, and there is a scope to improve health-care quality if this model is introduced across the country.